2011
DOI: 10.1002/bdm.689
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and reason in everyday risk perception

Abstract: Emotion in everyday risk perception 2 ABSTRACT Although research has documented the importance of emotion in risk perception, little is known about its prevalence in everyday life. Using the Experience Sampling Method, 94 part-time students were prompted at random -via cellular telephones -to report on mood state and three emotions and to assess risk on thirty occasions during their working hours. The emotionsvalence, arousal, and dominance -were measured using self-assessment manikins (Bradley & Lang, 1994). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 38 publications
4
16
1
Order By: Relevance
“…Inverse relations between judgments of risk and benefit have also been shown in experts' judgments (see Ganzach, 2000, for evidence with financial analysts, Slovic, MacGregor, Malmfors, & Purchase, 1999, for evidence with toxicology experts, and Savadori et al, 2004, for evidence with biotechnology experts). The effect of emotions on risk perception seems pervasive, as it is also found in randomly sampled behaviors from everyday life (Hogarth, Portell, Cuxart, & Kolev, 2011). In summary, empirical evidence suggests that perceptions of risk and benefit are related to the overall affect that a verbal description of a stimulus activates.…”
Section: The Role Of Affect In Judgments Of Risk and Benefitmentioning
confidence: 96%
“…Inverse relations between judgments of risk and benefit have also been shown in experts' judgments (see Ganzach, 2000, for evidence with financial analysts, Slovic, MacGregor, Malmfors, & Purchase, 1999, for evidence with toxicology experts, and Savadori et al, 2004, for evidence with biotechnology experts). The effect of emotions on risk perception seems pervasive, as it is also found in randomly sampled behaviors from everyday life (Hogarth, Portell, Cuxart, & Kolev, 2011). In summary, empirical evidence suggests that perceptions of risk and benefit are related to the overall affect that a verbal description of a stimulus activates.…”
Section: The Role Of Affect In Judgments Of Risk and Benefitmentioning
confidence: 96%
“…Compared to other measures of affect, such as Emocards [33] or smartphone applications, research participants find the SAM relatively easy to use and interpret [34, 35]. Unfortunately, despite the SAM’s widespread use for assessing emotional responses to stimuli, state norms are not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Redelmeier and Kahneman36 showed how patients’ memories of pain during a colonoscopy or lithotripsy (retrospective evaluation) did not match their judgement of pain during the actual procedure (contemporaneous evaluation). Studies of perceived risk have also shown that this is higher during than after an event 22,37…”
Section: Basic Requirements Of Research Methods For Studying Daily Lifementioning
confidence: 99%
“…Sense-making refers to people’s tendency to reinterpret their lives in the light of more recent events or to confirm implicit theories and beliefs. Finally, state of mind, or retrospections (particularly of affect and attitude) can reflect a person’s mood at the time of the report 37. These biases can be controlled for by having participants report in real time, but this also has limitations, such as registration errors.…”
Section: Basic Requirements Of Research Methods For Studying Daily Lifementioning
confidence: 99%